Do elite sailors perform better on cognitive tasks than academic scholars? - Chan, Victoria Jing Hua (2015)
The purpose of the study was to investigate the relationship between sailing expertise and perceptual cognitive skills, as measured by the component skills approach. It is hypothesized that Elite Sailors (ES) will demonstrate shorter inhibition, higher problem solving than Academic Scholars (AS) and that sailing expertise would minimize gender differences. Participants comprised of 15 ES and 17 AS who were tested for inhibition and problem solving, using cognitive tests of Stop Signal Task (SST) and Tower of London (TOL) respectively. To avoid potential confounding factors, additional self-reported scales and a vocabulary test to measure overall intelligence were used. The results showed that the main effect of group (Elite Sailor, Academic Scholar) in inhibition were marginally significant (p = 0.055), while the main effect of group (Elite Sailor, Academic Scholar) in problem solving were not significant statistically (p = 0.352). The interaction (Group x Gender) was not significant statistically for inhibition (p = 0.434) and problem solving (p = 0.669). The results suggest that participation in sailing by ES is not differently associated with cognitive functions of inhibition and problem solving compared to participation in non-sport activities by AS. In addition, there were no gender differences in inhibition and problem solving scores for both groups. This was inconsistent with the hypotheses of ES demonstrating shorter inhibition, higher problem solving than AS and that sailing expertise would minimize gender differences. Future studies may consider using different populations, larger sample size and a sport specific design. Key words: inhibition, problem solving, sailing